Kinetics of quality deterioration in dried carrots (Daucis carota Linn.) during storage - Falco, Maria Elsa M.; Acevedo, Teresita P. (2000)
The study was conducted to determine the quality deterioration in dried carrots using B-carotene as index or determinant during storage as function of time, type of packaging materials and temperature. The study shows that B-carotene degradation was directly related with the change in color of dried carrots during storage. The kinetics of B-carotene degradation in dried carrots during storage at different temperature follows the first-order reaction model. Degradation of B-carotene occurred faster for those packed in low density polyethylyne (LPDE) than those packed in metalized foil with vacuum (MFV) sealing during storage at ambient (30+-2C) temperature. There was no significant difference in terms of B-carotene retention and change in color on samples packed in metalized foil with vacuum (MFV) and without vacuum (MFA) sealing. The amount of B-carotene retained in samples packed in metalized foil with vacuum (MFV) and without vacuum (MFA) sealing after storage at 15C was found to be two times higher than those samples stored at 30C and three times higher than those samples stored at 40C. The estimated shelf life of dried carrots during storage at 15C, 30C, and 40C andpacked in MFA was 54, 23 and 16 weeks, respectively. MFV-packed dried carrots stored at 15C, 30C and 40C had an estimated shelf-life of 62, 24 and 13 weeks, respectively.
Thesis (M. S. Food Science)--University of the Philippines,Diliman.
Keywords: Carrots -- Storage -- Philippines; Carotenes -- Deterioration